2003
DOI: 10.1194/jlr.r300005-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol sulfate in human physiology: what's it all about?

Abstract: Cholesterol sulfate is quantitatively the most important known sterol sulfate in human plasma, where it is present in a concentration that overlaps that of the other abundant circulating steroid sulfate, dehydroepiandrosterone (DHEA) sulfate. Although these sulfolipids have similar production and metabolic clearance rates, they arise from distinct sources and are metabolized by different pathways. While the function of DHEA sulfate remains an enigma, cholesterol sulfate has emerged as an important regulatory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
186
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(191 citation statements)
references
References 125 publications
4
186
1
Order By: Relevance
“…In this study, we identified CS as a key molecule for the regulation of encystation. In mammals, the roles of CS in cellular functions are relatively well characterized (e.g., regulation of lipid metabolism, protection of erythrocytes from osmotic lysis, supporting platelet adhesion, and acting as a nuclear receptor ligand) (11,27). However, there have been few reports concerning CS, or even its production, in unicellular eukaryotes (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we identified CS as a key molecule for the regulation of encystation. In mammals, the roles of CS in cellular functions are relatively well characterized (e.g., regulation of lipid metabolism, protection of erythrocytes from osmotic lysis, supporting platelet adhesion, and acting as a nuclear receptor ligand) (11,27). However, there have been few reports concerning CS, or even its production, in unicellular eukaryotes (28).…”
Section: Discussionmentioning
confidence: 99%
“…CS, a constituent of cellular membranes, originally was isolated from human plasma, and its synthesis is mediated by an SULT that uses cholesterol and PAPS as substrates (10,11). To date, several genes for cholesteryl SULTs have been identified in mammals (10,12).…”
Section: Resultsmentioning
confidence: 99%
“…Cholesterol sulfate is present in various tissues and body fluids, and it accumulates during squamous cell differentiation in the epithelial cells of barrier tissues, such as the respiratory tract and esophageal mucosa (11,12,42). Cholesterol sulfate is also found in considerable quantities in the skin, predominantly in the epidermis (10), where it acts as an important regulator during the formation of the epidermal barrier (42).…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol sulfate is also found in considerable quantities in the skin, predominantly in the epidermis (10), where it acts as an important regulator during the formation of the epidermal barrier (42).…”
Section: Discussionmentioning
confidence: 99%
“…However, CS in its own right can act as a regulatory molecule 41,42 . Of the selected metabolites, CS was our only candidate that fitted into networks generated in Ingenuity pathway analysis ® (IPA).…”
Section: Identification Of Candidate Biological Moleculesmentioning
confidence: 99%